Association of Diverse Genotypes and Phenotypes of Immune Cells and Immunoglobulins With the Course of HIV-1 Infection - Li, Liuzhe; Liu, Yan; Gorny, Miroslaw K. (Frontiers in Immunology, 2018)
The variation of disease progression among HIV-1 infected individuals draws great interest in exploring the underlying mechanisms. Studies have demonstrated that many factors are involved in the distinct disease outcome from innate to adaptive immune response, cell-mediated to humoral mediated immune response, and genetic to phenotypic factors. All elements involving in disease outcome work in concert with each other. The present data suggest that the multifaceted factors in an infected individual should be considered as a whole instead of a unique element and the analysis should be dissected in more detail for meeting the requirement of personalized medicine and better guiding of vaccine design. However, contrary to the necessity of comprehensive investigation, a problem stems from the widely used ART treatment, which influences the implementation of the studies on systematic analysis of the HIV-1 infected population, resulting in fewer data to be acquired in the future. Given a limited number of treatment-naive HIV-1 infected individuals on the way, the review endeavors to recapitulate the distinct genotype and phenotype features of the immune system with a particular focus on the surface proteins on immune cells among individuals with different HIV infection outcomes.